PENGARUH CELEBRITY ENDORSER TERHADAP BRAND IMAGE PRODUK PADA IKLAN TEH KEMASAN - Nurtiah; Abdillah, Fatimah; Akbar, Muhammad (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
The high demand of food and beverage products make competitors so tight; consequently, companies are encouraged to be more creative in creating a brand association in the minds of consumers. By using celebrity endorsers in promotional activities, the company can form a brand image of its products. The purpose of this study was to determine the extent of the influence of celebrity endorser on brand image in tea product advertisements around Dramaga-Bogor. Data collection used purposive sampling techniques and questionnaire for 100 respondents. The study was tested using a linear regression analysis method through partial t-test by using SPSS 15.0. The results showed that the public perception around Dramaga Bogor District towards celebrity endorser in advertisement was very good, therefore it has a positive effect on brand image of the tea product.